Workplace friendship, employee well-being and knowledge hiding: The moderating role of the perception of Chaxu climate - He, Peixu; Wang, Jun; Zhou, Hanhui; Zhang, Chi; Liu, Qiyuan; Xie, Xin (Frontiers in Psychology, 2022)
In recent years, knowledge hiding has become a hot topic in the field of organizational behavior because of its great harm. However, relevant studies have focused only on the negative interpersonal antecedents of knowledge hiding but neglected the inhibition effect of positive informal relationships on the behavior. To fill this gap, the current study develops a moderated mediation model to investigate how and when workplace friendship has a negative impact on knowledge hiding. Drawing on social exchange theory(SET), we propose that workplace friendship inhibits knowledge hiding through the mediating role of employee well-being, with the Perception of Chaxu climate acting as a boundary condition. Using data from a two-wave time-lagged survey of 279 employees in China, the results show that workplace friendship has a negative impact on knowledge hiding behavior. Specifically, workplace friendship inhibits knowledge hiding by satisfied employee well-being, i.e., workplace friendship has a positive impact on employee well-being, while employee well-being has a negative impact on knowledge hiding. Perception of Chaxu Climate moderates the indirect effect, as the level of employee’s Perception of Chaxu climate rises, the direct effect of workplace friendship on employee well-being is stronger, so as the indirect effect of workplace friendship on knowledge hiding. This article explores the mechanisms affecting employee knowledge hiding from a new interpersonal perspective of workplace friendship. It is enlightened that firms should pay attention to the management of workplace friendship, provide employee with opportunities to establish workplace friendship while providing proper guidance on the direction of workplace friendship and improving the quality of it, in order to promote employees’ happiness perception and organizational knowledge management ability.